Measurement of K fluorescence analysis in ancient bone using X-ray transition edge sensor and semiconductor detectors - Zhi-Wei Li; Si-Ming Guo; Shuo Zhang; Jin-Jie Wu; Zhen Wang; Nan Li; Zhong-Tao Wang (European Physical Journal C: Particles and Fields)
Abstract Transition edge sensor (TES) have high energy resolution, which can extremely improve in various scientific experiments the energy spectrum analysis capability and have a wide range of applications in almost all fields covering the whole wave band of electromagnetic waves. The same Chinese ancient human bone sample was measured by fluorescence analysis using SDD, Si-PIN detector and TES detector. Typical representative results among the measurements of the three detectors were selected for comparative analyses. The experimental results showed that the TES detector has obvious advantages compared with the semiconductor detector, with a resolution of 21.2eV@3.69 keV, compared to 115.8 eV @ 3.69 keV and 143.9 eV @ 3.69 for SDD and Si-PIN detectors, respectively. TES detector even found some spectral lines that cannot be measured by semiconductor detectors, such as the 0.916 keV L line of Cu, L line of 2.86 keV Rh and so on. The experimental results demonstrate the TES detector’s outstanding performance in elemental spectral line detection. Compared to observations with semiconductor detectors, using X-ray TES enables clear resolution of spectral lines corresponding to elements present in the sample.